1985
DOI: 10.1136/jnnp.48.10.999
|View full text |Cite
|
Sign up to set email alerts
|

The near-nerve sensory nerve conduction in tarsal tunnel syndrome.

Abstract: SUMMARY The near-nerve sensory nerve conduction in the medial and lateral plantar nerves was studied in 25 cases of tarsal tunnel syndrome. Sensory nerve conduction was abnormal in 24 cases (96%) The most common abnormalities were slow nerve conduction velocities and dispersion phenomenon (prolonged duration of compound nerve action potentials). These two electrophysiological abnormalities are indicative of a focal segmental demyelination as the primary pathological process in tarsal tunnel syndrome.In 1979, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 4 publications
4
32
1
Order By: Relevance
“…In previous large epidemiological studies, the prevalence of symptomatic and electrodiagnostically confirmed CTS was approximately 2.1-4.9 % in the general population [27,28]. Seddon et al reported that the tarsal tunnel differs from the carpal tunnel in that the retinaculum of the former is thinner [29], which may render the nerve less compressible in the tarsal tunnel than in the carpal tunnel [30]. Thus, TTS appears to be a relatively rarer entrapment neuropathy than CTS (2.1-4.9 %).…”
Section: Discussionmentioning
confidence: 99%
“…In previous large epidemiological studies, the prevalence of symptomatic and electrodiagnostically confirmed CTS was approximately 2.1-4.9 % in the general population [27,28]. Seddon et al reported that the tarsal tunnel differs from the carpal tunnel in that the retinaculum of the former is thinner [29], which may render the nerve less compressible in the tarsal tunnel than in the carpal tunnel [30]. Thus, TTS appears to be a relatively rarer entrapment neuropathy than CTS (2.1-4.9 %).…”
Section: Discussionmentioning
confidence: 99%
“…This technique has the advantage of obtaining sensory nerve conduction in six branches derived from the medial and lateral plantar nerves. The technique was useful for the diagno- sis of tarsal tunnel syndrome, 15 medial plantar neuropathy, 17 lateral plantar neuropathy, 16 distal sensory neuropathy, 18 and early stage of diabetic sensory neuropathy. 20 It revealed a "definite neuropathy" pattern (abnormalities in more than three of six tested nerves) in 57.1% of the patients who had diabetic sensory neuropathy with normal routine NCS.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients, low sensory nerve action potentials (SNAPs) can be recorded by near-nerve needle techniques [19,20], e. g. from interdigital nerves (IDN) [21]. This underlines the importance of axon loss (axonopathy) in DN and argues in favor of additional analysis of the action potentials after nerve stimulation.…”
Section: Discussionmentioning
confidence: 98%